**Note:- 1) if y = x^n ; then dy/dx = n*x^(n-1)**

Thus,

If y = (1+4x)^(1/3) ; then

Let f(x) = x^(1/3)...........(1)

And g(x) = (1+4x).........(2)

Thus, f(g(x)) = (1+4x)^(1/3) .................Answer

Now, dy/dx = y' = (1/3)*{(1 + 4x)^(-2/3)}*4

or, dy/dx = (4/3)*[(1+4x)^(-2/3)]

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now